An Overview of Fast Dissolving Oral Thin Film - S. Muthukumar; R. Gayathri; A. Abarnadevika; C. Sanakr; Vinesha Ravi (Current Aspects in Pharmaceutical Research and Development Vol. 2, 2021)
Many pharmaceutical companies are switching their products from tablets to fast dissolving oral thin films (OTFs). Films have all the advantages of tablets (precise dosage, easy administration) and those of liquid dosage forms (easy swallowing, rapid bioavailability). Statistics have shown that four out of five patients prefer orally disintegrating dosage forms over conventional solid oral dosages forms. Pediatric, geriatric, bedridden, emetic patients and those with Central Nervous System disorders, have difficulty in swallowing or chewing solid dosage forms. Many of these patients are non-compliant in administering solid dosage forms due to fear of choking. OTFs when placed on the tip or the floor of the tongue are instantly wet by saliva. As a result, OTFs rapidly hydrate and then disintegrate and/or dissolve to release the medication for local and/or systemic absorption. This technology provides a good platform for patent non- infringing product development and for increasing the patent life-cycle of the existing products. The application of fast dissolving oral thin films is not only limited to buccal fast dissolving system, but also expands to other applications like gastroretentive, sublingual delivery systems.